DEVELOPMENT OF LEARNING MEDIA SCHOOLOGY BASED ON DISCOVERY LEARNING TO IMPROVE HISTORICAL ANALYSIS - Shohib Furqon Farizi; Nurul Umamah; Sumardi Sumardi (History Education, University of Jember, 2020)
Implementation of learning in the Industrial Revolution 4.0 is expected in the learning process using technology. The purpose of this research is to produce a validated product in the form of Schoology Learning media based on Discovery Learning and to improve the ability of Historical Analysis. The development research procedure is carried out using the ASSURE model development. The results of the subject matter content experts reached 80% with